2016
DOI: 10.1007/s10851-016-0674-4
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Morphology on the Spherical CIELab Quantale with an Application in Color Image Boundary Detection

Abstract: Mathematical morphology is a theory with applications in image processing and analysis. This paper presents a quantale-based approach to color morphology based on the CIELab color space in spherical coordinates. The novel morphological operations take into account the perceptual difference between color elements by using a distance-based ordering scheme. Furthermore, the novel approach allows for the use of non-flat structuring elements. An illustrative example reveals that non-flat dilations and erosions may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…A conditionally invariant mathematical morphological framework for color images was presented in [33], and a vector ordering method based on linear transformations from RGB to other color spaces and principal component analysis (PCA) were developed. Valle and Valente [34] proposed a quantal-based approach to color mathematical morphology based on the CIEL*a*b* color space in spherical coordinates. The definition of morphological operators used a distance-based ordering scheme and non-flat structuring elements.…”
Section: B Color Mathematical Morphologymentioning
confidence: 99%
“…A conditionally invariant mathematical morphological framework for color images was presented in [33], and a vector ordering method based on linear transformations from RGB to other color spaces and principal component analysis (PCA) were developed. Valle and Valente [34] proposed a quantal-based approach to color mathematical morphology based on the CIEL*a*b* color space in spherical coordinates. The definition of morphological operators used a distance-based ordering scheme and non-flat structuring elements.…”
Section: B Color Mathematical Morphologymentioning
confidence: 99%
“…In the last decades, different approaches to distance-based color MM have been proposed by prominent researchers including [1,2,8,14,20,26]. Despite successful applications, these approaches often face the difficult task of choosing a suitable reference for sorting vector values.…”
Section: Statistics Of Distance-based Morphological Operatorsmentioning
confidence: 99%
“…In this paper, we focus on a distance-based approach which have been investigated and generalized by many researchers including [1,2,8,14,20,[26][27][28]. Precisely, we focus on the distance-based approach to multivalued MM obtained by first comparing the distance between the value of a pixel and a reference value r followed by a lexicographical cascade to resolve ambiguities [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of vector-valued images, vector spaces endowed with a total order is one of the most comfortable frameworks for the extension of morphological processing [2,1,22]. Approaches that have been recently formulated using total orderings include [9,12,[18][19][20][21]. Despite their successful applications for color and hyperspectral image processing, Chevallier and Angulo showed that the information contained in a total order is too weak to reproduce the natural topology of the value space [5].…”
Section: Introductionmentioning
confidence: 99%